2014
DOI: 10.1212/wnl.0000000000000837
|View full text |Cite
|
Sign up to set email alerts
|

Stroke subtype, vascular risk factors, and total MRI brain small-vessel disease burden

Abstract: Objectives:In this cross-sectional study, we tested the construct validity of a “total SVD score,” which combines individual MRI features of small-vessel disease (SVD) in one measure, by testing associations with vascular risk factors and stroke subtype.Methods:We analyzed data from patients with lacunar or nondisabling cortical stroke from 2 prospective stroke studies. Brain MRI was rated for the presence of lacunes, white matter hyperintensities, cerebral microbleeds, and perivascular spaces independently. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
791
5
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 758 publications
(875 citation statements)
references
References 35 publications
26
791
5
5
Order By: Relevance
“…It is the most common cause of vascular dementia and causes approximately a fifth of the strokes worldwide [9], proven to have significant and strong associations with vascular risk factors [10]. A moderate-to-severe burden of PVS in the basal ganglia (BG) is one of the markers of SVD [9], along with lacunes, cerebral microbleeds and white matter hyperintensities (WMH).…”
Section: Introductionmentioning
confidence: 99%
“…It is the most common cause of vascular dementia and causes approximately a fifth of the strokes worldwide [9], proven to have significant and strong associations with vascular risk factors [10]. A moderate-to-severe burden of PVS in the basal ganglia (BG) is one of the markers of SVD [9], along with lacunes, cerebral microbleeds and white matter hyperintensities (WMH).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a recent study using an unweighted SVD scale recommended that different cutoff points and weighting for MRI features should be investigated. 10 Furthermore, it is important to consider whether each measure of CeVD, in any proposed scale, carries the same importance to patients 11 and whether differential weighting of each MRI feature are needed to optimally predict outcomes of clinical importance, such as cognition. Therefore, we have explored whether a weighted assessment of total CeVD burden can improve understanding of the cognitive consequences of CeVD.…”
mentioning
confidence: 99%
“…One difference between the present study and previous investigations presenting derivations and investigation of total SVD burden scores is that we present a single measure derived from a single imaging modality rather than measures obtained from different MRI markers of SVD. For example, (Huijts et al, 2013;Klarenbeek et al, 2013, and Staals et al (2014 previously used information from lacunar infarcts, WMH, CMB and enlarged perivascular spaces to obtain SVD burden scores. Our SVD burden score, DSEG θ, was related to all four conventional MRI markers of SVD used in this study (WMH load, TCVrepresenting cerebral atrophy, new lacunes and CMB), with an increase in DSEG θ being associated with higher SVD burden as measured by these markers.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this, Jokinen et al (2011) reported independent contributions of WMH and incident lacunes in predicting decline in EF and IPS. As MRI markers of SVD are often co-occur in individuals, recent efforts have been made to combine them into a unitary score of SVD burden (Huijts et al, 2013;Klarenbeek et al, 2013;Staals et al, 2015;Staals et al, 2014). Huijts et al (2013) and Staals et al (2014) used a score of SVD burden in which the presence of WMH, CMB, perivascular spaces and lacunar infarcts was summed to create a score between 0 and 4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation